Nurse Practitioners Aiding Frail Elderly Through Home Visits. (October 2013) - Duckworth, Joy M.; Repede, Elizabeth; Elliott, Lydia
By 2030, one in every eight people will be above age 65 and the worldwide population is projected to increase to one billion. Ages 85 and older are the fastest growing part of the aging population. New reforms like the Independence at Home Act and the Affordable Care Act make home care visits a more viable option. This literature review demonstrates nurse practitioners can provide home care visits as an extension of the medical home model. This will allow frail, elderly patients to receive quality patient-centered care in their home, thereby decreasing emergency room visits, rehospitalization, and workload on office-based primary care providers.